Sediment Quality of the SW Coastal Laizhou Bay, Bohai Sea, China: A Comprehensive Assessment Based on the Analysis of Heavy Metals - Gao, Xuelu (PLoS One, 2015)
Historically, the Bohai Sea is one of the most important fishing grounds in China. Yet, surrounded by one of the biggest economic rims of China, its ecological functions have been declining rapidly in recent two decades under the heavy anthropogenic impacts. The Laizhou Bay is the smallest one of the three main bays in the Bohai Sea. Owing to the rich brine deposits, chemical industries using brine as raw materials are booming in the southern coast of the Laizhou Bay, the scale of which ranks as the largest one in China. In order to monitor and assess the environmental quality, surface sediments were collected from the coastal waters of southwestern Laizhou Bay and the rivers it connects with during summer and autumn in 2012, and analyzed for heavy metals. Several widely adopted methods were used in the overall assessment of heavy metal pollution status and potential ecological risks in these sediments, and the data were analyzed to infer the main sources of the pollutants. The results showed that the remarkably high concentrations of heavy metals were almost all recorded in a small number of riverine sites. Cr, Cu, Ni and Zn were the main environmental threat according to the sediment quality guidelines. The marine area was generally in good condition with no or low risk from the studied metals and adverse effects on biota could hardly occur. Natural sources dominated the concentrations and distributions of Cu, Ni, Pb and Zn in the marine area. Our results indicated that heavy metal pollution was not a main cause of the ecological degradation of the Laizhou Bay at present.